Laser Doppler Vibrometer: Application of DOE/Taguchi Methodologies to Pyroshock Response Spectra - C. J. Litz (Shock and Vibration)
Statistical methodologies were employed for measuring and analyzing the explosively induced transient responses of a flat steel plate excited with shock. The application of design of experiment methodology was made to structure and test a Taguchi L9(32) full factorial experimental matrix (which uses nine tests to study two factors, with each factor examined at three levels) in which a helium-neon laser Doppler vibrometer and two piezocrystal accelerometers were used to monitor explosively induced vibrations ranging from 10 to 105 Hz on a 96 × 48 × 0.25 in. flat steel plate. Resulting conclusions were drawn indicating how these techniques aid in understanding the pyroshock phenomenon with respect to the effects and interrelationships of explosive-charge weight and location on the laser Doppler and contract accelerometer recording systems.